2016
DOI: 10.3892/etm.2016.3530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape seed proanthocyanidin on Alzheimer's disease in vitro and in vivo

Abstract: Grape seed proanthocyanidin (GSPA) consists of catechin, epicatechin and epicatechin gallate, which are strong antioxidants that are beneficial to health and may attenuate or prevent Alzheimer's disease (AD). In the present study, the effects of GSPA on pheochromocytoma (PC12) cell viability were determined using cell counting kit-8 and lactate dehydrogenase (LDH) assays, whereas apoptosis and mitochondrial membrane potential (Ψm) were measured via flow cytometry analysis. The effect of GSPA administration on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The obtained results are in consistency with the results of a study performed by Lian et al showed that Don group exhibited significantly decreased latency (P<0.01) and a significantly increased number of platform crossings (P<0.01), as compared with non-treated group. 30 Cognitive impairment of Scop is a result of destruction in cholinergic neurotransmission and increase of oxidative stress. 31 Thus, factors which are able to ameliorate these effects on cholinergic system and/or oxidative stress might be beneficial in AD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results are in consistency with the results of a study performed by Lian et al showed that Don group exhibited significantly decreased latency (P<0.01) and a significantly increased number of platform crossings (P<0.01), as compared with non-treated group. 30 Cognitive impairment of Scop is a result of destruction in cholinergic neurotransmission and increase of oxidative stress. 31 Thus, factors which are able to ameliorate these effects on cholinergic system and/or oxidative stress might be beneficial in AD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a preclinical study demonstrated that grape seed proanthocyanidin (GSPA), which consists of catechin, epicatechin and epicatechin gallate, can interrupt the aggregation of neurotoxic Aβ (Figure 4) [76]. Altogether these data suggest that polyphenols may have the potential to reduce protein aggregation, a phenomenon important in AD progression.…”
Section: Targeting Amyloid Aggregationmentioning
confidence: 94%
“…Anthocyanins were reported to activate the phosphorylation of anti-phosphorylated GSK3β at Ser 9, thereby possibly preventing GSK-3β-dependent tau hyperphosphorylation at Ser 413 and 404 [80]. GSPA is also able to decrease hyperphosphorylated tau deposition in APP/PS1 male heterozygous mice (Figure 4) [76].…”
Section: Targeting Tau Proteinmentioning
confidence: 99%
“…These include apocynin [66,67,68], baicalein [69], caffeine [70,71,109], curcumin [72,73,74], niacin [64], nicotine [64], pinocembrin [75,76,110], resveratrol [77,78,79,80,81,111], polyphenols [112], and tanshinone IIA [82,83,84]. However, the number of studies investigating the effects of these agents on neurodegeneration and cognitive performance is limited.…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 99%